MEREFLEKSIKAN KEMBALI KRISTOKRASI BERDASAKAN DIALOG YESUS DENGAN PILATUS DALAM PERIKOP YOH. 18:28-19:16 - Mayolla, Innoccentius Gerardo (Bahasa Indonesia, 2025)
This research focuses on exploring and reflecting the Christocratic values of Jesus' royal leadership obtained through theological reflection on the dialogue between Jesus and Pilate in John 18:28 – 19: 16. The dialogue between Jesus and Pilate is part of the story of Jesus' passion and resurrection. This one chapter of Jesus' life is very important to see the religious aspects of Jesus' leadership. Christocracy itself is a system of leadership or government based on Christ as the Head of the Church. The methodology used in this research is a qualitative methodology. This methodology is carried out with interpretive analysis and theological reflection on the text John 18: 28-19: 26. Text interpretation, critical analysis and theological reflection are also supported by an in-depth study of literature related to the topic of Christocracy, the meaning of the Kingdom of Christ and the dialogue between Jesus and Pilate. This research found that based on John 18: 28-19: 16 the character of Christ's kingly leadership or christocracy is centered on Christ himself, comes from divine religious values, aims at witnessing the truth, is willing to suffer for the truth and continues to listen to Jesus as the Lord, The Truth Itself.